Comparison of Guided Inquiry Learning Models with Direct Instruction Learning Models on Physics Learning Outcomes - Khoiro Lathifa; Hufri Hufri (Department of Physics Universitas Negeri Padang, 2023)
The teacher's capability to design and enforce learning plays an important role in student learning results. One manner that teachers can enhance learning results is by way of deciding on the right learning model in step with the learning objectives and material to be taught in class. The aim of this research is to determine the variations in physics learning results among college students taught using the guided inquiry learning model and college students taught using the direct instruction learning model in class XI SMAN 1 Padang. This kind of studies is quasi-experimental studies with a posttest only control design. The studies populace is class XI students of SMAN 1 Padang for the 2023/2024 academic year. Sample selection used purposive sampling technique. The sample for this research is class XI F.4 as experimental class 1 and class XI F.5 as experimental class 2. The research statistics is in the form of student studying results in the knowledge aspect. The data collection instrument is a take a look at instrument inside the form of multiple choices. The statistics analysis techniques used are descriptive evaluation, normality test, homogeneity test, and hypothesis test at a significance degree (α) = 0.05. Based on the consequences of studies statistics evaluation, the average learning outcomes of students in experimental class 1 were 76.67 and experimental class 2 was 69.86. Hypothesis testing was carried out on students' posttest scores and obtained t0 = 2,049 > ttable= 1,999 until H0 rejected and H1 established. It could be concluded that there’s a large distinction between college students who practice the guided inquiry learning model and college students who prectice the direct instruction learning model on vector material and rectilinear motion kinematics.